Epilepsy: From pediatric to adulthood. Definition, classifications, neurobiological profiles and clinical treatments - Giulio Perrotta (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2020)
This work focuses on the specific analysis of the general, neurobiological and clinical profiles of epileptic forms, starting from classifications and definitions, and then extending the field of study to clinical and symptomatological data, to conclude with treatments and better management of these patients.